Técnicas de prospecção e maturidade tecnológica para suportar atividades de P & D - Andrade, Herlandí de Souza [UNESP]; Chimendes, Vanessa Cristina Gatto; Rosa, Adriano Carlos Moraes; Silva, Messias Borges [UNESP]; Chagas, Milton de Freitas (My University, 2018)
Science and technology are considered as fundamental elements for economic and social development. For the innovation process investing in new knowledge has become essential for keeping organization in the market. Searching for new technologies and mapping of scientific and technological developments that can significantly influence an organization is the main role of technological prospecting. Technological prospecting has as one of its main objectives, the offering of subsidies to finance R & D activities. In this context, studying the techniques of technological prospection in a nucleus of innovation is relevant to leverage companies that work directly with technology. Thus, the objective of this article is to present a proposal for the application of technological prospecting tools to an R & D team. Considering that this work was conducted through bibliographic research, patent research, observation of activities and possible comparisons. After the studies it was verified that in the prospection of technology different methods should be used, since prospecting technology requires systemic vision, through monitoring, forecasting and vision of the future orienting the decision making relevant to the positioning of the business in the market.
Prospecting and technological readness level to support R & D activities
Keywords: Intellectual property; Research and development; Technological innovation; Technological prospecting